Comparative study of solar radiation at four sites of Nepal: A case study - Shrestha, Prakash M.; Gupta, Suresh P.; Rai, Krishna B.; Joshi, Usha; Chapagain, Narayan P.; Karki, Indra B.; Poudyal , Khem N. (Patan Prospective Journal, 2024)
Solar radiation data are of great important for solar energy systems. This study aimed to compare solar radiation at Manang, Kathmandu Valley, Nepalgunj and Biratnagar. Daily data of global solar radiation (Hg) measured by CMP6 pyranometer are received from Department of Hydrology and Meteorology of Nepal. Coefficient of variance, skewness, kurtosis and Fourier series are used to analyze the solar radiation. Daily, monthly and seasonal analysis are done. Global solar radiation are found maximum (18.6 ± 6.7 MJ/m2/day) at Manang and minimum (14.1 ± 4.1 MJ/m2/day) at Biratnagar. Solar radiation is more deviated at Manang whereas less deviated at Kathmandu Valley. Solar radiation is maximum in spring and minimum in winter at four sites. Hg is mostly seasonally dependent at Nepalgunj but less dependent at Biratnagar. The present research will help to advance the state of knowledge of global solar radiation in energy harvesting and agriculture.